A new multi-scale 3D-GIS-approach for the assessment and dissemination of solar income of digital city models. (May 2016) - Bremer, M.; Mayr, A.; Wichmann, V.; Schmidtner, K.; Rutzinger, M.
Abstract: In order to support an effective planning of solar panel constructions or passive energy measures, information of potential solar income has to consider multiple levels of scale and detail. It has to consider the regional and the detailed household scale. Recent developments in the field of digital city models and 3D GIS allow combining the advantages of both domains. We present a multi-scale 3D GIS approach for the assessment and dissemination of solar income of a digital city model. For the consideration of long and close range shadows, we combine polygonal geometries, 3D-voxel grids and 2.5D Digital Elevation Models of different resolutions in a multi-scale modelling scene. In order to allow a realistic assessment of the heterogeneous 3D shadowing patterns in urban environments, we present a texture mapping approach for homogeneous surface sampling and efficient data storage. The approach integrates the regional topographic context with detailed 3D assessments on a household scale. In order to show the capabilities of the presented approach, a performance test using different scene compilations was conducted. Comparing the performance of different geometrical representations of a city model tile in terms of computational effort and accuracy of the results, the relevance of high spatial resolutions and the consideration of full 3-dimensionality of the presented modelling approach is proven. The results are compatible to current 3D standards such as CityGML and COLLADA facilitating the dissemination of results to non-expert addressees. Highlights: A new GIS approach in order to sample 3-dimensional object surfaces for solar potential simulations. A texture mapping approach for 3D city models allowing flexible storage and dissemination of computed results. A combination of regional and local 3D solar potential assessment.